The effect of variable taq Polymerase concentrations in Polymerase chain reaction (PCR) / Zanura Adzhari - Zanura, Adzhari (Faculty of Health Science, 2007)
Prior to the discovery of a thermostable Taq polymerase, anyone conducting a PCR reaction procedure was obliged to sit patiently by a series of water baths or heating blocks to add a fresh aliquot of E.coli DNA polymerase after each denaturation step. This rather tedious step was eliminated by the introduction of the Taq polymerase. Despite its huge popularity, PCR has certain limitations and the efficiency of a PCR reaction will vary according to template, reaction buffer, dNTPs, primers, cycling temperature and numbers. In this study, Taq polymerase concentrations ranging from 0.5U to 8.0U were optimized to obtain the expected DNA target. The enzyme was diluted according to the study design; standard PCR profile was then performed with other PCR components remained unchanged throughout the study. The DNA products were then electrophoresed, stained, photographed by UV light and then analyzed. At low Taq polymerase concentration (0.5U), a faint band was seen and band intensity increased proportionate to the increase of Taq polymerase. However, at 8.0U of Taq polymerase concentration, the band intensity decreased. Therefore, the optimal Taq polymerase concentration is in the range of 2.0U to 4.0U per 50ul reaction in this particular PCR protocol. It is wiser to choose a lower Taq polymerase concentration and as Taq is an expensive reagent, this may save unnecessary additional cost. In future, other alternative heat-stable DNA polymerase like Pyrocococcus furionsus (Pfii) DNA polymerase and Thermococcus litoralis (VENT) may be worth considered as an alternative because of the proof-reading ability conferred by these new polymerases.